THE FREQUENCY OF FLT3 MUTATION IN FIFTY FIVE IRAQI ADULT PATIENTS WITH ACUTE MYELOID LEUKEMIA (Iraqi Journal of Medical Sciences, 2016)
Background:Mutations within the FLT3 gene, which code for the class-III-receptor kinase FLT3, ranked within the most frequent recurrent known genetic markers in acute myelocytic leukemia (AML). Internal tandem duplication (ITD) mutations in the juxtamembrane domain of FLT3 gene occur in 20-25% of AML.Objectives:This study designed to detect the frequency of FLT3-ITD mutation in adult AML patients, and to correlate the prevalence of this mutation with the clinical presentation of the patients and their response to induction therapy.Methods:The study comprised 55 AML patients and 33 healthy controls. For each patient, complete blood picture, blood film, bone marrow aspiration and biopsy was done. FLT3-ITD mutation was detected by conventional Polymerase Chain Reaction technology. Complete hematological remission achievement after induction chemotherapy was assessed by clinical examination and full laboratory investigations.Results:Out of 55 AML patients 8 (14.54%) had FLT3-ITD mutation and all of them presented as de novo AML. Moreover, 6 (75%) out of 8 mutated patients were newly diagnosed whereas 2 out of 8 were in relapse and were not on any therapy. The mean age of patients who had the mutation was lower than those without the mutation; also the majority of patients with mutation were male. The mean WBC count in mutated patients was not significantly higher than non-mutated patients. Higher bone marrow blast cell percent was found in mutated patients. FLT3-ITD mutation was mostly detected in M3 (37.5%) followed by M2 (25%), and lastly in M1 and M4 subtypes (12.5% for both subtypes) of FAB classification. Four out of 8 mutated patients failed to response to induction therapy although they were with good compliance to drug and 1/8 died throughout the induction therapy.Conclusion:Since FLT3-ITD mutation was associated with higher WBC count, significantly higher bone marrow blast cell percent and low rate of response to induction therapy; therefore it had been considered one of poor prognostic factor. It is a factor in defining risk stratification of AML patients.Keywords: AML, FLT3-ITD mutation, conventional PCR, FAB sub-types
Keywords: AML; FLT3ITD mutation; conventional PCR; FAB subtypes